2022
DOI: 10.3390/ijerph191912421
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Mixture of Perfluoroalkyl Substances and Lipid Profile in a Highly Exposed Adult Community in the Veneto Region

Abstract: Background: Residents of a large area in the Veneto Region (Northeastern Italy) were exposed to drinking water contaminated by perfluoroalkyl substances (PFAS) for decades. While exposure to PFAS has been consistently associated with elevated serum lipids, combined exposures to multiple PFASs have been poorly investigated. Utilising different statistical approaches, we examine the association between chemical mixtures and lipid parameters. Methods: Cross-sectional data from the regional health surveillance pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 33 publications
9
18
0
Order By: Relevance
“…An additional method for assessing two measurement techniques involves examining their relationship to a common third variable. In our study, we opted to use cholesterol levels, as prior research has established connections between at least PFOS and PFOA levels and cholesterol levels 17–20 . The evaluation of both abundances from nontargeted analysis and concentrations from conventional assays in relation to cholesterol yielded strikingly similar Speakmans' rho values.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…An additional method for assessing two measurement techniques involves examining their relationship to a common third variable. In our study, we opted to use cholesterol levels, as prior research has established connections between at least PFOS and PFOA levels and cholesterol levels 17–20 . The evaluation of both abundances from nontargeted analysis and concentrations from conventional assays in relation to cholesterol yielded strikingly similar Speakmans' rho values.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, the main aim of the current study is to compare absolute plasma concentrations of PFAS obtained by protein precipitation and matrix matched calibration isotope dilution UHPLC–MS/MS with semiquantitative relative concentration measurements performed on the same plasma samples using a widely used commercial nontargeted platform. Further, numerous prior studies have reported an association between perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) concentrations and cholesterol levels 17–21 . Therefore, we aimed to compare the relationship of PFOA and PFOS obtained from these two assays with total cholesterol levels.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chen et al, 2020 53 (Continued ) 81,[100][101][102] In the large studies, total serum PFAS and individual PFAS (PFOA, PFHxS, and PFOS) also were found to be associated with higher HDL-C, but in the small studies, PFOA was reported to be associated with lower HDL-C concentrations in exposed versus control participants or not associated with HDL-C. 81,[100][101][102] Total serum PFASs were not found to be associated with serum triglycerides, but PFOA and PFHxS (not PFNA or PFOS) were reported to be linked with increased serum triglycerides. 81,[100][101][102] Analysis of participants from a contaminated community in Sweden (3760 participants) also reported associations between PFOA, PFHxS, and PFOS and higher total cholesterol, LDL-C, and HDL-C. 103 Null associations were reported for PFAS and triglycerides. 103 Cross-sectional studies in North America have analyzed associations between PFAS and serum lipids in the general population and contaminated communities.…”
Section: Dyslipidemia and Atherosclerosismentioning
confidence: 99%
“…Cross-sectional studies in multiple countries have investigated associations between PFAS and serum lipids with strong associations in contaminated communities in Europe, North America, Asia, and Australia. Cross-sectional analyses (from small [97 participants] to large [34 633 participants]) in the contaminated area of the Veneto Region (Italy) consistently demonstrated that total serum PFAS and individual PFAS (PFOA, PFNA, PFHxS, and PFOS) are associated with higher total serum cholesterol and LDL-C. 81,100–102 In the large studies, total serum PFAS and individual PFAS (PFOA, PFHxS, and PFOS) also were found to be associated with higher HDL-C, but in the small studies, PFOA was reported to be associated with lower HDL-C concentrations in exposed versus control participants or not associated with HDL-C. 81,100–102 Total serum PFASs were not found to be associated with serum triglycerides, but PFOA and PFHxS (not PFNA or PFOS) were reported to be linked with increased serum triglycerides. 81,100–102 Analysis of participants from a contaminated community in Sweden (3760 participants) also reported associations between PFOA, PFHxS, and PFOS and higher total cholesterol, LDL-C, and HDL-C. 103 Null associations were reported for PFAS and triglycerides.…”
Section: Pfas and Cvd Risk Factorsmentioning
confidence: 99%